2022
DOI: 10.1080/09593985.2022.2028325
|View full text |Cite
|
Sign up to set email alerts
|

The effect of kinesiophobia on physical activity, balance, and fear of falling in patients with Parkinson’s disease

Abstract: Purpose: Kinesiophobia is defined as the fear of movement and activity resulting from a feeling of vulnerability to painful injury or re-injury. This study aimed to determine the effect of kinesiophobia on physical activity, balance, and fear of falling in patients with Parkinson's disease. Methods: The study, which was designed as a cross-sectional type, was conducted with 86 patients with Parkinson's disease (age 61.25 SD [9.72] years old) by face-to-face interviews with the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2026
2026

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In line with the current study, prior research has demonstrated no relationship between self-reported measures of physical activity and kinesiophobia in primary health care patients with musculoskeletal pain ( 56 ), younger adults with temporomandibular disorder ( 57 ), and patients with chronic neck pain ( 58 ). However, significant research has also found that greater kinesiophobia is associated with lower levels of self-reported physical activity in individuals with knee osteoarthritis ( 14 , 15 ), non-specified chronic pain ( 59 ), chronic low back pain ( 60 ), Parkinson's Disease ( 61 ), and a general adult population ( 18 ). It remains unclear why such discrepant results exist regarding the relationship between self-reported physical activity and kinesiophobia, but the wide variety of self-reported measures likely plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the current study, prior research has demonstrated no relationship between self-reported measures of physical activity and kinesiophobia in primary health care patients with musculoskeletal pain ( 56 ), younger adults with temporomandibular disorder ( 57 ), and patients with chronic neck pain ( 58 ). However, significant research has also found that greater kinesiophobia is associated with lower levels of self-reported physical activity in individuals with knee osteoarthritis ( 14 , 15 ), non-specified chronic pain ( 59 ), chronic low back pain ( 60 ), Parkinson's Disease ( 61 ), and a general adult population ( 18 ). It remains unclear why such discrepant results exist regarding the relationship between self-reported physical activity and kinesiophobia, but the wide variety of self-reported measures likely plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…No studies were found relating fear of falling and depression with fear of movement in individuals with lower limb lymphedema. However, studies carried out in other pathological conditions show that both the fear of falling ( 9 , 10 , 27 , 67 ) and depression ( 13 , 31 , 39 ) can be related to kinesiophobia. The coexistence of fear of falling and fear of movement has been demonstrated in people with Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, the relationship between pain and fear of movement has been widely studied, and this symptom may effectively be the determining factor for this difference. However, people with lymphedema may experience signs and symptoms, such as fatigue ( 18 , 52 , 53 ), decreased balance ( 19 , 27 , 54 ), reduced physical performance ( 17 , 19 ) fear of falling ( 27 , 55 ), and depression ( 26 , 56 61 ), and appear in the literature in association with kinesiophobia ( 9 , 18 , 19 , 26 , 27 , 31 ). Movement avoidance is common among people with fatigue regardless of the pathological condition creating it ( 18 , 62 – 64 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations